(untitled) (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2025)
Enterprise social media usage is increasingly being recognized as an important technical tool used in the workplace, yet limited research has been conducted on its impact on employee satisfaction. To fill this gap, this study aims to investigate the relationship between enterprise social media usage and job satisfaction in the perfume sector in Saudi Arabia. A quantitative research methodology was employed, which was empirically validated through an online survey conducted with 300 employees in the Saudi perfume industry. The results support the proposed hypotheses and reveal that enterprise social media usage positively influences job satisfaction. These results contribute to the limited literature on enterprise social media usage in Saudi Arabia and provide practical insights for managers in the perfume industry. Managers and perfume companies can utilize these findings to instruct their employees on the effective use of social media, thereby enhancing job satisfaction.